Direct Vicinal Difunctionalization of Alkynes: An Efficient Approach Towards the Synthesis of Highly Functionalized Fluorinated Alkenes. Issue 13 (5th February 2015) - Besset, Tatiana; Poisson, Thomas; Pannecoucke, Xavier
Abstract: The direct vicinal difunctionalization of versatile alkynes is an area of considerable interest. In particular, the concomitant introduction of a functional group and a fluorinated moiety offers new efficient synthetic routes to the construction of highly functionalized olefins, key building blocks in the synthesis of several complex and relevant molecules. This review highlights the major progress that has been made in this field offering an overview of the direct concomitant introduction of a range of functional groups and various fluorinated moieties into alkynes through radical and metal‐catalyzed processes. In addition, rearrangement reactions involving molecules containing alkynes and leading to fluorinated alkenes are also carefully depicted. Abstract : The concomitant introduction of fluorinated groups and an additional functional group into alkynes has attracted considerable attention as an efficient synthetic route towards polyfunctionalized fluorinated olefins. This microreview focuses on the major progress achieved in this field involving transition‐metal‐catalyzed transformations and radical processes.